1981
DOI: 10.1128/aem.41.3.729-736.1981
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic Acid Production by Penicillium brevicompactum on Solid Media

Abstract: When grown on Czapek-Dox agar, Penicillium brevicompactum produced mycophenolic acid after a vegetative mycelium had been formed and as aerial hyphae were developing. Nutrients were still plenteous in the agar when the synthesis began. If aerial hyphal development was prevented by placing a dialysis membrane over the growing fungus, no mycophenolic acid was produced. When the dialysis membrane was peeled back and, as a consequence, production of aerial hyphae began, mycophenolic acid biosynthesis was observed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Growth and maintenance of the organism. P. brevicompactum Dierckx (ATCC 9056) was maintained, subcultured, and grown on Czapek-Dox glucose-containing agar slants and petri dishes (10 cm) as described previously (2,9). "On-agar," "over," "between," and "stripped-between" cultures were prepared as indicated previously (2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth and maintenance of the organism. P. brevicompactum Dierckx (ATCC 9056) was maintained, subcultured, and grown on Czapek-Dox glucose-containing agar slants and petri dishes (10 cm) as described previously (2,9). "On-agar," "over," "between," and "stripped-between" cultures were prepared as indicated previously (2).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of solid cultures for nutrients: assay of biomass wet weight and light microscopy. The procedures for assay of biomass wet weight and light microscopy have been described previously (2). For epifluorescence microscopy, the Nikon epifluorescence attachment was employed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initiation of biosynthesis is usually restricted to a specific developmental stage or to specialized cells within the organism. In Penicillium brevicompacturn, mycophenolic acid, brevianamide A, asperphenamate and ergosterol were simultaneously synthesized with development of aerial hyphae (Bartman et al 1981). Wang and Yang (1995) indicated that short-rod mycelial fragments of S. rimosus in the stationary phase had high oxytetracycline production capability in submerged cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of the organism. P. brevicompactum Dierckx (ATCC 9056) was maintained and grown in a solid culture on Czapek-Dox glucose-based agar as described previously (1). "Between" cultures were prepared as described previously (1), using 4.6 x 106 spores per 10-cm petri plate.…”
Section: Methodsmentioning
confidence: 99%